What if life were a dream? Reflections from Zubiri’s philosophy - Alberdi Sudupe, Jesús; Alberdi Páramo, Íñigo (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
Life is nothing but a dream. From Heraclitus and Parmenides to our days, the hypothesis that we only live within the dreams of a universal spirit or will has received philosophical attention at different historical moments. We live in a dream. Heraclitus distinguishes a world unique to each individual, in which we immerse ourselves when we sleep and dream, from a world largely shared with others when we are awake. We live in two worlds, dreams, and wakefulness. Zubiri speaks of human processes of unrealization of the contents apprehended in the formality of reality presented to us in primary apprehension. It is the provisional construction of unreal worlds, but always from the reality in which we are already installed. Unrealization is not synonymous with non-reality. It is unrealization from and within reality. Dreaming and fantasizing, constructing specters and fictions, are some types of unrealization. We live solely in reality, and within it, we can fantasize and dream. Although it may not be a metaphysical impossibility, in our view, the initial hypothesis that all life is nothing but a dream can receive at least two criticisms. On the one hand, it is an idea based on attributing a human capacity, that of being able to dream or fantasize, to other metaphysical instances beyond humans, be they Brahman or universal spirit or will. Something debatable. On the other hand, some characteristics of our real life do not fit well with being only part of a dream in which we are being dreamed. Pain, some forms of love, among other human experiences in which we trust. And if these criticisms were true, life would be something more than a dream.